2009
DOI: 10.1038/bmt.2008.432
|View full text |Cite
|
Sign up to set email alerts
|

KIR genes and KIR ligands affect occurrence of acute GVHD after unrelated, 12/12 HLA matched, hematopoietic stem cell transplantation

Abstract: Interactions of polymorphic killer Ig-like receptor (KIR) receptors with KIR ligands have been shown to modify the outcome of hematopoietic SCT (HSCT). The association of these genetic factors with different transplantation endpoints, however, varies substantially, depending on clinical and study setup variables. We aimed to assess whether KIR ligands, KIR genes and KIR haplotypes are associated with HSCT outcome of 124 patients with various hematological malignancies, transplanted with 12/ 12 HLA matched graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 37 publications
3
30
1
1
Order By: Relevance
“…7 A recent study reported that a missing HLA-C2 ligand for donor inhibitory KIR2DL1 was significantly associated with an increased risk of acute GVHD. 38 Our findings provide evidence of an association of high expression of KIR2DL1/3DL1 in the early stage after transplantation with aGVHD. Although the effect of KIR expression on the occurrence of GVHD seemed significant in our study, this hypothesis needs to be further confirmed in an expanded cohort of patients.…”
Section: Discussionmentioning
confidence: 51%
“…7 A recent study reported that a missing HLA-C2 ligand for donor inhibitory KIR2DL1 was significantly associated with an increased risk of acute GVHD. 38 Our findings provide evidence of an association of high expression of KIR2DL1/3DL1 in the early stage after transplantation with aGVHD. Although the effect of KIR expression on the occurrence of GVHD seemed significant in our study, this hypothesis needs to be further confirmed in an expanded cohort of patients.…”
Section: Discussionmentioning
confidence: 51%
“…These KIR haplotypes also affect the clinical outcomes of HSCT, but the impacts are variedly or sometimes inconsistently reported. 18,24,25 On the basis of the above controversy and discrepancy, the present study investigated a panel of 116 patients at our center with different hematological malignancies and the effect of KIR genes and missing KIR ligands on the clinical outcome of URD-HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies are probably linked to heterogeneous patient populations, differences in the sources of stem cells and various conditioning regimens. 17,18 In addition to the inhibitory KIRs and HLA class I molecules, the potential clinical significance of activating KIRs, for which the ligands and functions are not well identified, 19 is receiving increasing attention. The presence of the KIR2DS2 gene in the donor has been associated with a high risk of mortality following URD-HSCT, 20 whereas the presence of two activating KIRs, 2DS1 and 2DS2, in the donor has been significantly associated with a decreased leukemic relapse rate.…”
Section: Introductionmentioning
confidence: 99%
“…According to the authors, a consequence of this finding may be an increased alloreactivity of the host against graft, impairing the response of donor cells resulting in an insufficient graft-versus-leukemia effect and increased risk of leukemic relapse. Nowadays, there is no unequivocal evidence that polymorphic genes for KIR involved in innate immunity sufficiently influence GvHD and transplant outcome to change clinical practice (Davies et al, 2002;Cooley et al, 2009;Giebel et al, 2003;Hsu et al, 2005;Ludajic et al, 2009;Miller et al, 2007;Moretta et al, 2009;Schellekens et al, 2008;Symons et al, 2010;Witt et al, 2006). Using a large cohort of patients, Venstrom et al (2010) demonstrated that individual donor activating KIR, recipient HLA class I ligands, and donor KIR gene copy number all impact KIR-driven NK effects.…”
Section: Impact Of Killer Immunoglobulin-like Receptors and Hematopoimentioning
confidence: 99%